EFFICACY OF BENZNIDAZOL TREATMENT IN TRYPANOSOMA CRUZI INFECTED CHILDREN: A RANDOMIZED DOUBLE BLIND CLINICAL TRIAL CONDUCTED IN CENTRAL BRAZIL - Andrade, ALSS; Zicker, Fabio; Silva, AS; Oliveira, RM; Luquetti, AO; Almeida, IC; Travassos, LR; Rassi, A; Andrade, JG; Andrade, SS; et al. (Revista de Patologia Tropical / Journal of Tropical Pathology, 2007)
EFFICACY OF BENZNIDAZOL TREATMENT IN TRYPANOSOMA CRUZI INFECTED CHILDREN: A RANDOMIZED DOUBLE BLIND CLINICAL TRIAL CONDUCTED IN CENTRAL BRAZIL